The “Sagrada Familia” of Gaudí: Communion of Images and People - Curti, Chiara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
The temple of Sagrada Familia by Gaudí constitutes the contemporary paradigm of how Christian art can communicate universally. This paper presents a work supported by original photographs and based on testimonies of collaborators of Gaudí on the will to communicate the expiatory temple of the Sagrada Familia through the life of the people. Characteristic of a work that from the iconographic point of view does not provide essential novelties, but rather transmits a creativity that emerges from a communional life.